Islamic Fintech and Indonesian MSMEs during the Pandemic - Vira Amalia Putri; Nimas Melenia Mutiara Akbary (Sebelas Maret Business Review, 2021)
The COVID-19 pandemic has had a tremendous impact on Micro, Small, and Medium Enterprises (MSMEs). MSMEs are required to be able to adapt to existing business developments by using technological adaptation. This study aims to investigate Islamic Financial Technology (Islamic Fintech) as the alternative financing for the MSMEs. The use of Islamic Islamic Fintech is considered crucial, looking at the Muslim population in Indonesia. Islamic Fintech is the provision of financial services based on Islamic principles that bring together or connect financiers with financing recipients to carry out financing contracts through an electronic system using the internet network. Islamic Fintech could make financial services cheaper, faster, and easier. The method used in this research is the descriptive analysis method with a qualitative approach. In this paper, we find that Islamic Fintech can play a role in facilitating business actors in obtaining funding based on Islamic principles.